Pengaruh Kualitas Makanan Terhadap Kepuasan Wisatawan serta Dampaknya Terhadap Loyalitas Wisatawan di Objek Wisata Pantai Padang - Naseh Ulwan; Yulia Mandasari (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
This study aims to see the effect of food quality on tourist satisfaction and to see its impact on tourist loyalty at Padang Beach Tourism Object. This type of research is quantitative descriptive with Path Analysis method. The population in this study is the number of tourists visiting the city of Padang in 2021 as many as 1,002,270. The sampling technique was carried out by purposive sampling method and using the Slovin formula, obtained a sample of 99 samples. Data was collected using a Likert scale that had been tested for validity and reliability. The results showed that: 1) Food Quality variable had a positive and significant effect on tourist satisfaction variables with a value of sig0.000<0.005 and an r-square value of 0.628 means that 62.8% of tourist satisfaction depends on the quality of food available at the Padang beach tourism object 2) The tourism variable has a positive and significant effect on the tourist loyalty variable with a value of sig0.000<0.005 , 3) The food quality variable has a positive and significant effect on the tourist loyalty variable with a sig value of 0.000 <0.005, 4) the food quality variable has no significant effect on the tourist loyalty variable.